Proceso de ASC - APLICACIONES DE LA ARCILLA AUTOMOTRIZ O DE PROTOTIPADO EN EL DISEÑO Y FABRICACION DE MODELOS Y/O PROTOTIPOS (2020)
“Industrial or prototyping clays” (Industrial Clay) are materials malleable and moldable to make three-dimensional models; and offer great versatility; since they can be worked either manually (sculpted) or digital (CNC routed); and due to their properties it is possible to use and reuse them again, without having to waste material or discard already made models during the process. This ability to modify its structure allows it to used as a molding material for different applications and fields among them, arts and design; especially in the early and final stages of the process planning and development of new products. For this reason it is used widely in the automotive and consumer products industry; to define the aesthetic and visual characteristics of the product (shape and embodiment). EAFIT recently developed an industrial clay with similar characteristics to imported ones (Automotive Clay) and with local components; with which obtained an invention patent from the SIC; with the name: “PROCESS FOR THE OBTAINING INDUSTRIAL CLAYS FOR PROTOTYPING AND CLAYS OBTAINED” ; with IP number IPC Classification: C04B 33/36; of sep. of 2019. The present project; For its part, it aims through the use of said development; and its interaction with other materials and end-use processes; identify possible uses of this, in the manufacture of parts, molds or casings for models and prototypes of vehicles or others; through processes such as thermoforming, materials compounds, resin casting and so on. All of the above, with the purpose of defining and establishing key variables for the replicability of said processes, using clay or CLAY as a material for different types of molds and parts.